Express yourself? Henrietta Maria and the political value of emotional display at the Stuart court. Issue 2 (3rd March 2020) - Griffey, Erin
ABSTRACT: Through an investigation of letters, accounts and artworks, this article demonstrates how Queen Henrietta Maria's emotions were carefully calibrated to conform to conventions of appropriate behaviour and to maximise benefits that were both personal and dynastic, political and financial. The queen's emotional display is considered within the gendered and political contexts of the Stuart and Bourbon courts, from the time of her marriage to her death. The discussion positions Henrietta Maria's emotional performances within a series of key life moments which were accompanied by textual, ceremonial, material and visual commemoration. Whether showing joy at the dynastic coup of her marriage and birth of healthy children, or the misery of the queen whose servants were dismissed or "la reine malheureuse" – the widow and the martyr queen – Henrietta Maria's emotional display was politically charged.